Accuracy of the Yamax CW-701 Pedometer for measuring steps in controlled and free-living conditions. (June 2016) - Coffman, Maren J; Reeve, Charlie L; Butler, Shannon; Keeling, Maiya; Talbot, Laura A
Objective: The Yamax Digi-Walker CW-701 (Yamax CW-701) is a low-cost pedometer that includes a 7-day memory, a 2-week cumulative memory, and automatically resets to zero at midnight. To date, the accuracy of the Yamax CW-701 has not been determined. The purpose of this study was to assess the accuracy of steps recorded by the Yamax CW-701 pedometer compared with actual steps and two other devices. Methods: The study was conducted in a campus-based lab and in free-living settings with 22 students, faculty, and staff at a mid-sized university in the Southeastern US. While wearing a Yamax CW-701, Yamax Digi-Walker SW-200, and an ActiGraph GTX3 accelerometer, participants engaged in activities at variable speeds and conditions. To assess accuracy of each device, steps recorded were compared with actual step counts. Statistical tests included paired sample t -tests, percent accuracy, intraclass correlation coefficient, and Bland–Altman plots. Results: The Yamax CW-701 demonstrated reliability and concurrent validity during walking at a fast pace and walking on a track, and in free-living conditions. Decreased accuracy was noted walking at a slow pace. Conclusions: These findings are consistent with prior research. With most pedometers and accelerometers, adequate force and intensity must be present for a step to register. The Yamax CW-701 is accurate in recording steps taken while walking at a fast pace and in free-living settings.